2023
DOI: 10.1002/ueg2.12398
|View full text |Cite
|
Sign up to set email alerts
|

Similar geographic distributions of death rates from inflammatory bowel disease and Hodgkin lymphoma or multiple sclerosis

Abstract: Background: A previous comparative analysis of the time trends of Hodgkin lymphoma (HL), multiple sclerosis (MS), Crohn's disease (CD), and ulcerative colitis (UC) suggested that the occurrence of all four diseases was precipitated by exposure to similar environmental risk factors during early lifetime. In the present cross-sectional study, it was hypothesized that besides their resembling temporal variations the four diseases would also show similar geographic distributions.Methods: Using the vital statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition, similar geographic distributions of IBD and MS reflect on the potential influence of a shared environmental risk factor [8]. A more recent epidemiologic study of their world-wide distributions again revealed strikingly similar geographic patterns and significant correlations amongst all 4 diagnoses [9]. This recent study also suggested that the exposure to any relevant environmental risk factors must have started before the age of 5 years in UC and HL and before the age of 15 years in CD and MS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar geographic distributions of IBD and MS reflect on the potential influence of a shared environmental risk factor [8]. A more recent epidemiologic study of their world-wide distributions again revealed strikingly similar geographic patterns and significant correlations amongst all 4 diagnoses [9]. This recent study also suggested that the exposure to any relevant environmental risk factors must have started before the age of 5 years in UC and HL and before the age of 15 years in CD and MS.…”
Section: Discussionmentioning
confidence: 99%